SAN PEDRO: ANALYSIS OF THE PROVINCIAL MUNICIPAL MANAGEMENT MARCH 2020- FEBRUARY 2021, SAN PEDRO NEIGHBORHOOD OF THE HISTORICAL CENTER OF CUSCO - PERÚ - Catacora Valencia, Mara (2025)
This article evaluates the management of the Provincial Municipality of Cusco in the Barrio de San Pedro (SG-6) during the COVID-19 emergency (March 2020–February 2021). The objective was to analyze its effectiveness in a context of crisis that affected historic cities dependent on tourism. The methodology included identifying heritage subjects, interviewing key actors, and analyzing management components. The results revealed weaknesses in the municipal response to the fall in tourism and confinement. The conclusions highlight the need for more resilient strategies to improve management in historic cities in the face of global crises.